HUBUNGAN STRES AKADEMIK DENGAN KUALITAS TIDUR PADA MAHASISWA KEPERAWATAN UNIVERSITAS UDAYANA - Tari, Made Ayu Tara Sania; Kamayani, Made Oka Ari; S, Made Rini Damayanti (Coping: Community of Publishing in Nursing; Vol 10 No 2 (2022): April 2022, 2022)
Academic stress is stress related to educational activities. The cause of academic stress is the inability of individuals to make adjustments to academic demands. There are factors influence sleep quality such as academic stress. This study aimed at identifying the relationship between academic stress and sleep quality among nursing students at Udayana University. This was a quantitative correlative study using a cross-sectional design. The research sample in this study was 163 respondents who were selected by stratified random sampling technique. The independent variable of this study is academic stress while the dependent variable is sleep quality. The data were collected by the Educational Stress Scale for Adolescents (ESSA) dan Pittsburgh Sleep Quality Index (PSQI) questionnaires. The results showed 55 students (33,7%) had very high academic stress and 118 students (72,4%) had poor sleep quality. Data were analyzed using Spearman Rank correlation test. The result of the correlation test showed that there was a relationship between academic stress and sleep quality with a weak correlation and the direction of the correlation was positive (r = 0,236; p = 0,002), which means the higher the academic stress, the worse the sleep quality.